Aspek Hukum Hak Cipta Terhadap Buku Elektronik (E-Book) Sebagai Karya Kekayaan Intelektual - Muchtar Anshary Hamid Labetubun (SASI, 2018)
Intellectual Property Rights basically have economic value. Therefore it is not excessive if the results of human intellectual work are given adequate legal protection. Through this way Intellectual Property Rights will get a decent place as one form of rights that has economic value. E-Book is included as a protected work because it is an adaptation of the initial creation in the form of a book that each has its own copyright after being realized in a real form.